Magnetic Concentric Hot-Circle Generation at Optical Frequencies in All-Dielectric Mesoscale Janus Particles - Oleg V. Minin; Song Zhou; Cheng-Yang Liu; Jelene Antonicole Ngan Kong; Igor V. Minin (Nanomaterials, 2022)
The development of all-dielectric structures with high magnetic response at optical frequencies has become a matter of intense study in past years. However, magnetic effects are weak at optical frequencies due to the small value of the magnetic permeability of natural materials. To this end, natural dielectric materials are unemployable for practical “magnetic” applications in optics. We have shown for the first time that it is possible to induce intense magnetic concentric subwavelength “hot circles” in a dielectric mesoscale Janus particle. The basis of the Janus particle is a combination of the effects of a photonic jet, whispering-gallery waves, and the concept of solid immersion. Simulations show an (H/H0)2/(E/E0)2 contrast of more than 10, and maximal magnetic field intensity enhancement is more than 1000 for a wavelength-scaled particle with a refractive index n < 2 and a size parameter in the order of 30. This work may provide a new way to realize precise magnetic devices for integrated photonic circuits and light–matter interaction.